Seismic data analysis : processing, inversion, and interpretation of seismic data - Yilmaz, Özdoğan (Investigations in geophysics ;, 2001)
Öz Yilmaz has expanded his original volume on processing to include inversion and interpretation of seismic data. In addition to the developments in all aspects of conventional processing, this two-volume set represents a comprehensive and complete coverage of the modern trends in the seismic industry-from time to depth, from 3-D to 4-D, from 4-D to 4-C, and from isotropy to anisotropy.